Cancer mortality and congenital anomalies in a region of Italy with intense environmental pressure due to waste. Issue 11 (4th May 2009) - Martuzzi, M; Mitis, F; Bianchi, F; Minichilli, F; Comba, P; Fazzo, L
Abstract : Objectives: Waste management in the Campania region has been characterised, since the 1980s, by widespread uncontrolled and illegal practices of waste dumping, generating concerns over the health implications. The objective of this study was to evaluate possible adverse health effects of such environmental pressure. Methods: The health effects of waste-related environmental exposures in Campania were assessed in a correlation study on nine causes of death (for the years 1994–2001) and 12 types of congenital anomaly (CA) (1996–2002) in 196 municipalities of the provinces of Naples and Caserta. Poisson regression was used to analyse the association between health outcomes and environmental contamination due to waste, as measured through a composite index, adjusting for deprivation. Results: Statistically significant excess relative risks (ERR, %) in high-index compared with low-index (unexposed) municipalities were found for all-cause mortality (9.2 (95% CI 6.5 to 11.9) in men and 12.4 (9.5 to 15.4) in women and liver cancer (19.3 (1.4 to 40.3) in men and 29.1 (7.6 to 54.8) in women). Increased risks were also found for all cancer mortality (both sexes), stomach and lung cancer (in men). Statistically significant ERRs were found for CAs of the internal urogenital system (82.7 (25.6 to 155.7)) and of the central nervous system (83.5 (24.7 to 169.9)). Conclusion: Although the causal nature of the association is uncertain, findings support the hypothesis that waste-related environmental exposures in Campania produce increased risks of mortality and, to a lesser extent, CAs.